Detection and clinical significance of serum EPO levels in patients with haematological tumours: EPO levels in patients with haematological tumours - Zhao, Yanan; Zhang, Wenlong; Cong , Dan; Bai , Yuansong (Cellular and Molecular Biology, 2022)
This experiment aimed to detect serum erythropoietin (EPO) levels in patients with haematological tumours and to investigate its clinical significance. For this purpose, 110 patients with haematological tumours admitted to our hospital between January 2019 and December 2020 were selected as the study population according to the inclusion and exclusion criteria, and they were included in the case group, and the clinical data of the patients were retrospectively analysed. 90 cases of people without hematological tumors who underwent physical examination during the same period were also included as a control group. The serum EPO levels of the two study groups were compared, and the clinical diagnostic value of EPO was analysed using the subject operating characteristic curve (ROC). Results indicated that of the 110 patients, 56 were leukaemia patients, 24 were multiple myeloma patients and 30 were malignant lymphoma patients. The differences in gender, age, disease history, alcohol consumption and smoking history between the two groups were not significant (P>0.05), while the EPO levels in the control group were significantly lower than those in the case group, with a statistical significant difference of P<0.05. The EPO levels in patients with leukaemia, multiple myeloma and malignant lymphoma were (165.43± 20.46) mU/mL, ( 28.14± 4.51) mU/mL and (86.25±10.33) mU/mL significantly higher than the control group, with a significant difference of P<0.05. Using the absence of haematological tumours as a control, the analysis yielded an area under the ROC curve of 0.995 for EPO diagnosis in patients with leukaemia, a 95% confidence interval of 0.987 to 1.000, a sensitivity of 97.80%, with a sensitivity of 98.2 %; the area under the ROC curve for patients with multiple myeloma was 0.910, with a 95% confidence interval of 0.818 to 1.000, with a sensitivity of 98.90% and specificity of 87.50%; the area under the ROC curve for patients with malignant lymphoma was 0.992, with a 95% confidence interval of 0.978 to 1.000, with a sensitivity of 96.70% and specificity of 96.70%. In conclusion, the serum EPO levels of patients with haematological tumours are significantly higher than those of the normal population, and the detection of serum EPO levels is valuable for the diagnosis of clinical haematological tumours.